2012
DOI: 10.1155/2012/292140
|View full text |Cite
|
Sign up to set email alerts
|

Stomach Metastasis in a Patient with Prostate Cancer 4 Years after the Initial Diagnosis: A Case Report and a Literature Review

Abstract: Prostate cancer commonly metastasizes bones and lymph nodes, but it very rarely spreads to the gastrointestinal tract. However, only five cases of prostate cancer metastatic to the stomach have been previously reported in the literature. We report a case of a 69-year-old man with metastatic prostate cancer who presented with upper gastrointestinal bleeding (UGB) 4 years after the diagnosis. Esophagogastroscopy revealed multiple ulcerations in the gastric body and histopathological examination confirmed gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…Gastric metastasis is followed by other metastatic lesions. 4 , 5 However, in this case we only found a gastric lesion, and CT and bone scintigraphy did not reveal any metastatic lesions. To the best of our knowledge, a solitary gastric metastasis arising from a prostate tumor has not been reported to date.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Gastric metastasis is followed by other metastatic lesions. 4 , 5 However, in this case we only found a gastric lesion, and CT and bone scintigraphy did not reveal any metastatic lesions. To the best of our knowledge, a solitary gastric metastasis arising from a prostate tumor has not been reported to date.…”
Section: Discussionmentioning
confidence: 50%
“…Gastric metastasis often arises from high-risk prostate cancer. 4 , 5 The initial PSA level was 7.61 ng/ml and the Gleason score of the prostatectomy was 3 + 4. Bilici et al reported a gastric metastasis arising from a prostate tumor with a Gleason score of 3 + 4, 5 but the PSA level was 244.8 ng/ml before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic gastric tumor of prostate cancer is rare and only 13 cases have been reported to date [2][3][4][5][6][7][8][9][10][11][12][13][14]. Time to metastasis to the stomach from a diagnosis of primary prostate cancer varies (identified simultaneously to 10 years later).…”
Section: Discussionmentioning
confidence: 99%
“…Among other cancers, bone and the lung are the most common distant metastatic sites in prostate cancer, which is rarely observed in the stomach/bowel (1.8%) [2]. Thirteen cases of metastatic prostate cancer to the stomach were reported in the English literature to date [3][4][5][6][7][8][9][10][11][12][13][14]. Most were diagnosed by biopsy with immunohistochemistry (IHC) of prostatespecific antigen (PSA), but only one case diagnosed as primary gastric cancer because of negative PSA staining was resected endoscopically [12].…”
Section: Introductionmentioning
confidence: 99%
“…Six of the patients were known to have prostate cancer prior to the diagnosis of gastric metastases, and prostate cancer was diagnosed in one patient after upper endoscopy with biopsy and confirmation on immunohistochemical staining 8-13. Although rare, metastases to other sites in the GI tract, such as the small bowel and esophagus, have been reported 14,15.…”
Section: Discussionmentioning
confidence: 99%